Perupaan Karakter Mang Ohle di Koran Pikiran Rakyat Sebagai Realita Pemikiran Rakyat di Jawa Barat - Triyadi, Agus (Jurnal Bahasa Rupa, 2017)
The caricature as part of the drawing works has a straightforward language, verbal, social criticism but is funny and intriguing. The presence of Mang Ohle caricature as a documentation and social criticism characteristic of innocent but smart, such as fictional Sundanese figures are very populist, namely Kabayan, while caricature is critical, satirical, but not make people angry. The Cartoonist Didin Basoeni has a principle, "Herang caina beunang laukna", which means "when the water clear, it is easier to look at the fish". That is, make criticism that avoids conflict. In this article disclosed the analysis of strategy of Mang Ohle characterization as the agent of the people voice in conveying their aspiration in the Pikiran Rakyat newspaper printed edition.